Understanding the reflection, challenges, and method for improvement in service learning at Universiti Teknologi Malaysia - Janius, N. (The Mattingley Publishing Co. Inc., 2020)
Service Learning (SL) has become an essential approach in education by bridding the community and students through experiental learning activities. Universiti Teknologi Malaysia (UTM) is one of the prominent institution that apply this approach and keep on improving the implementation in their curriculum. This research has three objectives such as to understand the reflections, to examine the challenges and proposed a systematical method for improvement in SL at UTM. A qualitative method was carried out in collecting the data of the study.Five undergraduate and five postgraduate students were interviewed and selected based on purposeful sampling and the research data was analyzed using NVIVO 17 software. Based on the research finding, the students were able to connect and analyzed the experience they had with and what they had learned during participated in SL activities along with community through the process of reflections in all areas such as conducted different types of SL project, management with community, changes in attitude, participants from community, exposure from faculty, cultivating personal values, commitment among group members and good planning of SL project. Despite the success of identifying three aspects that become challenges in conducting SL projects such as tight budget, limited time and lack of guidelines, these research also successfully proposed four systematic methods for improvement in SL such as provide guidelines, location, theme in SL and brainstorming. Overall, it is important to realize that implementing SL is not just about addressing and helping the community or students, but SL is a noble practice that requires dedication, high commitment, and cooperation from all parties to make this SL project beneficial to all and for the future.